Antibacterial Activity of -guaiene Patchouli Oil on Eschericia coli and Pseudomonas aeruginosa - Sekar Widyaningrum (Gontor AGROTECH Science Journal, 2020)
Patchouli oil is a commodity that has potential in the health sector where the chemical compound α-guaiene contained has the potential to be antibacterial. This study aims to determine the presence of antibacterial activity at α-guaiene (purity 37.5%) with a certain concentration against Eschericia coli (ATCC 25922) and Pseudomonas aeruginosa (ATCC 27853) and to determine the interaction between the α-guaiene concentration factor and the tested bacteria to the diameter of the formed resistance. This study used an experimental method with well diffusion test in Food Microbiology Laboratory of the Faculty of Agricultural Industrial Technology, Padjadjaran University. The concentrations of α-guaiene used were 20%, 40%, 60%, 80%, and 100% with meropenem and amoxicillin positive control and n-hexane negative control. The results of this study showed that the largest average diameter of inhibition, namely 3,22 mm in Eschericia coli was produced from α-guaiene with a concentration of 80% and 2,83 mm in the Pseudomonas aeruginosa bacteria was produced from 100% concentration of α-guaiene. The diameter of the inhibitory power formed at various concentrations of α-guaiene is classified into the resistant category.